Standard and escalating treatment of chronic inflammatory demyelinating polyradiculoneuropathy - Yoon, Min-Suk (SAGE Publications, 2011)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired, immune-mediated polyradiculoneuritis that is progressive or relapsing over a period of at least 8 weeks. Although the exact pathogenesis is unclear, it is thought to be mediated by both cellular and humoral immune reactions directed against the peripheral nerve myelin or axon. CIDP also involves spinal nerve roots. Early medical treatment of CIDP is important to prevent axonal loss. Only three treatment regimens for CIDP have demonstrated benefit in randomized, controlled studies: corticosteroids, plasma exchange, and intravenous immunoglobulins (IVIg). Approximately 25% of patients respond inadequately to corticosteroids, plasma exchange or IVIg. Large placebo-controlled trials with alternative immunosuppressive compounds, e.g. mycophenolate mofetil, cyclosporine, cyclophosphamide, or monoclonal antibodies, are lacking.